Nuevas perspectivas de las fuentes de información para la Geografía Industrial - Alonso Santos, José Luis; Aparicio Amador, Javier; Sánchez Hernández, José Luis (Geographicalia, 2016)
Nuevas perspectivas de las fuentes de información para la Geografía Industrial